Social Networks and Civic Participation and Efficacy in Two Evangelical Protestant Churches - Schwadel, Philip (Review of religious research, 2016)
This research note examines the proposition that participation in churchparticularly the social interaction that accompanies church participationis an important source of social capital that promotes civic activity and efficacy. Employing survey data from over 600 attendees of two evangelical Protestant churches, we tested hypotheses linking churchgoers' social networks to their levels of civic efficacy and participation. Three key findings emerged. First, the number of friends in church was positively associated with churchgoers' civic efficacy, religious civic activity, and secular civic activity, while the number of friends outside of church was unrelated to these outcomes. Second, the association between in-church networks and secular civic activity was partially mediated by civic efficacy. Third, church attendance moderated the association between in-church friends and secular civic activities such that high attending churchgoers with few in-church friends were far less likely to participate in secular civic activities. Taken together, these findings illustrate the importance of in-church social networks for Evangelical Protestants' civic participation and feelings of civic efficacy, in contrast to out of church social networks which had little overall impact on these factors.